Fatal poisonings involving propoxyphene before and after voluntary withdrawal from the United States' market: An analysis from the state of Florida. (November 2017) - Delcher, Chris; Chen, Guanming; Wang, Yanning; Slavova, Svetla; Goldberger, Bruce A.
Highlights: Propoxyphene-involved deaths declined 84% two years following market withdrawal. Propoxyphene has been detected in recent deaths and other drug data sources. Drug surveillance should continue post-withdrawal with a systematic phase-out. Abstract: The synthetic opioid propoxyphene was a schedule IV controlled substance with multiple reported health risks before the US Food and Drug Administration issued a request for voluntary market withdrawal in November 2010. The purpose of this study is to investigate the characteristics and occurrences of propoxyphene-related deaths in Florida before and after voluntary market removal. Decedent-level toxicology data from Florida's Medical Examiners Commission was used to compare the temporal, polysubstance use, sociodemographic, and geographic profiles associated with propoxyphene-involved deaths for a pre-withdrawal (November 2008–November 2010) and post-withdrawal (December 2010–December 2012) period. Sensitivity analyses using multiple data sources, including Florida's Prescription Drug Monitoring Program and other states' data, were conducted to examine potential reporting bias. Results showed that the number of propoxyphene-involved deaths declined by 84% from 580 deaths to 92 deaths after market withdrawal. The co-occurrence of other prevalent drugs, such as oxycodone (17.2% to 26.1%, p = 0.0422) increased significantly in the post-withdrawal study period. A larger proportion of the propoxyphene-related deaths were reported from South Florida after the withdrawal (28.4% to 56.5%, p < 0.0001). No significant changes in age and race/ethnicity were observed. Sensitivity analyses revealed that several deaths occurred in other states after market withdrawal, as recently as 2016. Our findings are consistent with previous studies that propoxyphene was still available after removal from the US market. Continued surveillance is recommended after highly abused opioids are withdrawn from the market due to on-going safety risks.